2008
DOI: 10.3171/foc/2008/24/2/e18
|View full text |Cite
|
Sign up to set email alerts
|

Techniques in carotid artery surgery

Abstract: ✓The major objective in carotid endarterectomy is to achieve safe and complete removal of intimal plaque and provide lasting, nonstenotic closure. Controversy exists as to which technical variation best achieves this. In this paper, the authors review the operative nuances and outcomes with conventional and eversion endarterectomy, with a focus on the latter. The views expressed reflect specific neurosurgical and vascular perspectives in the context of a multi-disciplinary stroke unit, where carotid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 78 publications
0
3
0
1
Order By: Relevance
“…Although CEA is very common and has been performed for more than 50 years, 9 the specific surgical technique is variable from surgeon to surgeon with respect to the use of general or local anesthesia, eversion or conventional endarterectomy, use of intraoperative shunt and carotid artery patching. [10][11][12][13] In addition, there is no agreement on the appropriate orientation of the surgical incision. The standard operative approach uses an incision oriented parallel with the anterior border of the sternocleidomastoid muscle.…”
mentioning
confidence: 99%
“…Although CEA is very common and has been performed for more than 50 years, 9 the specific surgical technique is variable from surgeon to surgeon with respect to the use of general or local anesthesia, eversion or conventional endarterectomy, use of intraoperative shunt and carotid artery patching. [10][11][12][13] In addition, there is no agreement on the appropriate orientation of the surgical incision. The standard operative approach uses an incision oriented parallel with the anterior border of the sternocleidomastoid muscle.…”
mentioning
confidence: 99%
“…This was a technical problem that would not have improved with anticoagulation and would need to be repaired regardless of the symptomatic status. In the past, we have treated these patients with reoperation and often have found that this complication can be either treated or avoided altogether through the usage of circumferential, vertically oriented tack-up sutures using 6-0 prolene at the site where the distal plaque is fractured from the intima 10 11. The decision on open versus endovascular treatment in this case was both technical and practical.…”
Section: Discussionmentioning
confidence: 96%
“…These are eversion and conventional CEA. 16 It has been shown that any incision applied to the vessel wall causes some degree of fibrosis as a natural part of the healing process, and this occurs despite the most meticulous care and use of fine suture materials. 17 In some instances, even vascular plasty techniques or the use of patch materials may result in restenosis due to vascular incisions.…”
Section: Experience Of 352 Carotid Endarterectomy Cases Operated On Wmentioning
confidence: 99%